Fresh electricity business cold chain logistics development and countermeasures research - Li, Jingwen; Ouyang, Yiting (International Journal of Global Economics and Management, 2024)
Under the background of new retail, fresh electricity business as a rising star of electricity business is developing rapidly, how to improve the service quality of fresh cold chain logistics, transportation efficiency, and further improve the market competitiveness of fresh cold chain logistics industry has gradually become the focus of attention. This paper expounds the necessity of the development of fresh electricity logistics, analyzes the main problems in the development of fresh cold chain logistics, the current fresh electricity cold chain logistics development strategy, how to promote the green and healthy development of fresh electricity cold chain logistics to provide countermeasures.